2018
DOI: 10.1016/j.pt.2018.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Trypanosomatids Are Much More than Just Trypanosomes: Clues from the Expanded Family Tree

Abstract: Trypanosomes and leishmanias are widely known parasites of humans. However, they are just two out of several phylogenetic lineages that constitute the family Trypanosomatidae. Although dixeny - the ability to infect two hosts - is a derived trait of vertebrate-infecting parasites, the majority of trypanosomatids are monoxenous. Like their common ancestor, the monoxenous Trypanosomatidae are mostly parasites or commensals of insects. This review covers recent advances in the study of insect trypanosomatids, hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
141
0
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 144 publications
(168 citation statements)
references
References 72 publications
(102 reference statements)
3
141
0
9
Order By: Relevance
“…The family Trypanosomatidae encompasses parasites of vertebrates, invertebrates, or plants [1]. Chagas disease, leishmaniasis, and human African trypanosomiasis are human diseases caused by Trypanosoma cruzi, Leishmania spp.…”
Section: Introductionmentioning
confidence: 99%
“…The family Trypanosomatidae encompasses parasites of vertebrates, invertebrates, or plants [1]. Chagas disease, leishmaniasis, and human African trypanosomiasis are human diseases caused by Trypanosoma cruzi, Leishmania spp.…”
Section: Introductionmentioning
confidence: 99%
“…are dixenous parasites, i.e. they have two different hosts in their life cycle [2,3]. The flagellated extracellular promastigotes develop in the gut of insect vectors, while the intracellular non-flagellated amastigotes occupy the phagolysosomes of vertebrates' macrophages [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Genes and gene products, governing differentiation or infection maintenance, are putative virulence factors. At present, they are identified primarily by the next-generation sequencing (NGS)-based approaches [3,6] and analyzed using functional genomics [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that 2′‐ O ‐methylations play a key role in cellular discrimination of endogenous from pathogenic RNA . Although various modifications of these caps have been discovered, surprisingly, the most complex methylation pattern known in nature was found in early eukaryotes, more precisely, within the Trypanosomatidae family from the Trypanosomatida order and the Kinetoplastida class . The relevant cap‐4 shows seven additional methylations in the first four nucleotides relative to cap‐0 (Figure ) …”
Section: Introductionmentioning
confidence: 99%